2018
DOI: 10.1002/ppul.24210
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled antibiotic use is associated with Scedosporium/Lomentospora species isolation in cystic fibrosis

Abstract: Introduction: Prevalence of fungi has been rising in the cystic fibrosis (CF) population.Scedosporium species (spp) is the second most common mold seen in the CF respiratory tract. However, the characteristics associated with Scedosporium isolation and its clinical implications are poorly understood. The goal of this study was to determine clinical factors associated with Scedosporium spp to better understand the mechanisms that may contribute to the emergence of filamentous fungi in CF. Methods:We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
4
11
0
Order By: Relevance
“…isolation in patients with CF. 10 This American retrospective cohort study found that FEV 1 % predicted was not associated with Scedosporium spp. isolation (odds ratio 0.99, 95% CI 0.96–1.04), which is in line with our findings (1.00, 0.99–1.01).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…isolation in patients with CF. 10 This American retrospective cohort study found that FEV 1 % predicted was not associated with Scedosporium spp. isolation (odds ratio 0.99, 95% CI 0.96–1.04), which is in line with our findings (1.00, 0.99–1.01).…”
Section: Discussionmentioning
confidence: 93%
“…isolation (odds ratio 0.99, 95% CI 0.96–1.04), which is in line with our findings (1.00, 0.99–1.01). 10 An Australian single centre study did not find a difference in FEV 1 between patients with and without Scedosporium spp. either.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations